PERKEMBANGAN CABANG MUHAMMADIYAH METRO PUSAT BIDANG DAKWAH PENDIDIKAN TAHUN 2006-2019 - Ratna Widya Sari; Kuswono Kuswono (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
This study aims to determine and analyze how the history of the formation of the Central Metro Muhammadiyah Branch then analyze the development of the Central Metro Muhammadiyah Branch in the field of da'wah education in 2006-2019. This research method is historical, data and data sources obtained from books in accordance with research studies, and Muhammadiyah figures as sources. Data collection techniques, namely literature study, interviews, and documents. The validity of the data was carried out by means of internal criticism and external criticism. The result of this research is that in 2006-2019 the development of da'wah at the Central Metro Muhammadiyah Branch in the field of education has increased in terms of quality and quantity. It can be concluded that the increase in da'wah in the field of education is the result of the hard work of the Central Metro Muhammadiyah Branch Management as well as the commitment and effort of the Muhammadiyah school educators, then the use of the right strategy.